The Effect of Government Expenditure Effectiveness in Health, Environmental, and Social Protection Function on the Achievement of Sustainable Development Goal 3 in Indonesia - Sucakni, Rahmadani Inem; Din, Muhammad; Furqan, Andi Chairil; Darmawan, I Putu Edi (Dinasti Publisher, 2026)
This study aims to analyze the influence of government functional expenditure in the health, environment, and social protection sectors on the achievement of Sustainable Development Goals (SDG) 3 which focuses on health and welfare aspects. This study uses panel data from 2020-2022 with a purposive sampling approach. Data was obtained from 526 district/city governments in Indonesia, resulting in a total final sample of 1,578 observations. Using multiple linear regression analysis, the results show that government functional expenditure in the health and environment sectors has a positive and significant influence on the achievement of SDG 3. However, expenditure on social protection functions has a significant negative influence. These findings indicate that the increase in government functional expenditure in the three sectors is followed by changes in the achievement of SDG 3. Although there have been many studies examining the relationship between government functional expenditure and public welfare, research integrating these three strategic sectors simultaneously is still relatively limited. Therefore, this research implies that the achievement of health and well-being requires meaningful investment and effective governance. This emphasizes the importance of improving the quality of transparent, efficient, and targeted public expenditure to support the optimal achievement of SDG 3. Further research is recommended to add other variables and extend the study period to obtain more comprehensive results.